DAMPAK DIGITALISASI PERTANIAN TERHADAP TINGKAT EKONOMI MASYARAKAT PETANI DI KECAMATAN ADILUWIH DAN GADINGREJO PRINGSEWU - Aulia Zakia Chulwa; Muhammad Zainal Ibad; Adinda Sekar Tanjung (Jurnal Perencanaan dan Pengembangan Kebijakan, 2022)
The majority of Indonesia's population lives in rural areas so that agriculture is the main sector in the economy and the survival of rural communities where it is known that the national income generated from the agricultural sector is more than 50%. To increase the effectiveness and efficiency of agricultural activities, the application of technology, especially digital-based ones, is very necessary because it has a significant impact on improving the economy of farming communities in particular, one of which is the digitalization of agriculture.Based on the results of descriptive statistical analysis, it is known that the application of agricultural digitization in terms of the use of applications used as online marketing media in Adiluwih and Gadingrejo sub-districts is still relatively low. The low use of this application is due to several factors that influence the use of agricultural applications, including farmer readiness factors, age factors, gender factors, education factors, extension factors, and income factors. Furthermore, this agricultural digitization has an impact on the economic level of the farming community, although it is still relatively low, this digitalization can increase farmers' income by 8.5%. This increase in income is obtained from the marketing of agricultural products through online media which is part of the digitalization tools in agriculture. This is an opportunity so that the application of digitalization and information technology in agriculture can be developed optimally in order to increase the economic growth of rural communities.